2015
DOI: 10.3390/e18010008
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet Energy and Wavelet Coherence as EEG Biomarkers for the Diagnosis of Parkinson’s Disease-Related Dementia and Alzheimer’s Disease

Abstract: Abstract:Parkinson's disease (PD) and Alzheimer's disease (AD) can coexist in severely affected; elderly patients. Since they have different pathological causes and lesions and consequently require different treatments; it is critical to distinguish PD-related dementia (PD-D) from AD. Conventional electroencephalograph (EEG) analysis has produced poor results. This study investigated the possibility of using relative wavelet energy (RWE) and wavelet coherence (WC) analysis to distinguish between PD-D patients;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 52 publications
(58 reference statements)
2
31
0
1
Order By: Relevance
“…In those studies, distinctions in spectral slowing features between AD and other dementias are identified for vascular dementia [ 26 , 39 , 130 ], frontotemporal dementia (FTD) [ 37 , 130 , 175 , 176 ], Lewy body dementia (DLB) [ 130 , 176 ], and Parkison's disease dementia (PDD) [ 130 ]. Moreover, disparity in synchronization measures is reported between AD, PDD [ 38 , 42 ], DLB and FTD [ 42 ]. Additionally, a combined model of EEG and MRI improved discrimination between AD and DLB [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In those studies, distinctions in spectral slowing features between AD and other dementias are identified for vascular dementia [ 26 , 39 , 130 ], frontotemporal dementia (FTD) [ 37 , 130 , 175 , 176 ], Lewy body dementia (DLB) [ 130 , 176 ], and Parkison's disease dementia (PDD) [ 130 ]. Moreover, disparity in synchronization measures is reported between AD, PDD [ 38 , 42 ], DLB and FTD [ 42 ]. Additionally, a combined model of EEG and MRI improved discrimination between AD and DLB [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…The most utilized layout is the international 10-20 system, commonly consisting of 21 electrodes; higher density variants of the 10-20 system such as 10-10 and 10-5 systems are utilized as well, usually with 64 and 128 electrodes, respectively, [ 30 ] as well as the alternative layouts Maudsley [ 31 ] and Geodesics positioning systems [ 32 ]. In recent years, quantitative EEG (qEEG, henceforth simply EEG) has been proven to be a reliable clinical tool for the diagnosis and study of illnesses and cortical disorders such as Huntington disease [ 33 ], autism spectrum disorders [ 34 ], epilepsy and seizure [ 35 ], cerebral ischemia [ 36 ], frontotemporal dementia [ 37 ], and Parkinson's disease dementia [ 38 ]. Furthermore, the differential diagnosis between AD and other diseases that lead to dementia as vascular brain injury [ 39 , 40 ] and Lewy body diseases [ 41 , 42 ] was assessed with EEG.…”
Section: Introductionmentioning
confidence: 99%
“…In the DNSI approach, oscillations in LFPs were represented with WP coefficients through a WP transform. Oscillations with high amplitude and regular patterns were assigned larger WP coefficients, while those with low amplitude and random patterns were assigned smaller WP coefficients (Donoho & Johnstone, ; Jeong, Kim, Song, Chung, & Jeong, ; Luo et al., ). A state discrimination model with a statistically optimal adaptive threshold and discrimination strategy was used to classify the coefficients into two classes.…”
Section: Methodsmentioning
confidence: 99%
“…It is the time-frequencyspace by successively convolving the time series with scaled and translated versions of a wavelet function. This waveletbased coherence measurement is deliberately significant in the contribution of the functional brain connectivity and, using specifications that anticipate the brain activity involved in a particular cognitive action [24].…”
Section: Brain Connectivity Estimation Using Wavelet Coherence (Wc)mentioning
confidence: 99%